Effect of tetrahedral DNA nanostructures on LPS‐induced neuroinflammation in mice - Yang, Xiao; Zhang, Fan; Du, Yue; Cui, Weitong; Dou, Yikai; Lin, Yunfeng; Zhao, Zhihe; Ma, Xiaohong (Chinese chemical letters, 2022)
Neuroinflammation plays a significant role in inducing depression-like behavior. Tetrahedral DNA nanostructures (TDNs) are molecules that exhibit anti-inflammatory properties and can effectively penetrate the blood-brain barrier. Thus, researchers have hypothesized that TDNs regulate the secretion of proinflammatory cytokines and consequently alleviate depression-like behavior. To test this hypothesis, we investigated the effect of TDNs on the depression-like behavior of C57 mice induced by lipopolysaccharide (LPS). We performed open-field, tail suspension, and sucrose preference tests on LPS- and LPS/TDN-treated mice. The results indicated that the injection of TDNs into LPS-treated mice resulted in increased velocity, center zone duration, frequency to the center zone, and sucrose preference, and decreased immobility time. Immunofluorescence results indicated that peripheral administration of LPS in the mice activated inflammation, which culminated in distinct depression-like behavior. However, TDNs effectively alleviated the inflammation and depression-like behavior through the reduction of the expression levels of proinflammatory cytokines, such as interleukin-1β and tumor necrosis factor-α in the brain. Additionally, TDNs normalized the expression level of microglia cell activation markers, such as ionized calcium binding adaptor molecule 1, in the hippocampus of mice. These results indicated that TDNs attenuated the LPS-induced secretion of inflammatory factors and consequently alleviated depression-like behavior. TDNs attenuated the LPS-induced secretion of inflammatory factors and consequently alleviated depression-like behavior. [Display omitted]